Calculation of hygroscopic particle deposition in the human lung. (February 2014) - Winkler-Heil, Renate; Ferron, George; Hofmann, Werner
Abstract Context: Inhaled hygroscopic aerosols will absorb water vapor from the warm and humid air of the human lung, thus growing in size and consequently changing their deposition properties. Objective: The objectives of the present study are to study the effect of a stochastic lung structure on individual particle growth and related deposition patterns and to predict local deposition patterns for different hygroscopic aerosols. Materials and methods: The hygroscopic particle growth model proposed by Ferron et al. has been implemented into the stochastic asymmetric lung deposition model IDEAL. Deposition patterns were calculated for sodium chloride (NaCl), cobalt chloride (CoCl2 · 6H2O), and zinc sulfate (ZnSO4 · 7H2O) aerosols, representing high, medium and low hygroscopic growth factors. Results: Hygroscopic growth decreases deposition of submicron particles compared to hydrophobic particles with equivalent diameters due to a less efficient diffusion mechanism, while the more efficient impaction and sedimentation mechanisms increase total deposition for micron-sized particles. Due to the variability and asymmetry of the human airway system, individual trajectories of inhaled particles are associated with individual growth factors, thereby enhancing the variability of the resulting deposition patterns. Discussion and conclusions: Comparisons of model predictions with several experimental data for ultrafine and micrometer-sized particles indicate good agreement, considering intersubject variations of morphometric parameters as well as differences between experimental conditions and modeling assumptions.